The prevalence of online food delivery service usage and its association with anthropometric measurements in Muscat, Oman; a cross-sectional study - Ahmed Yahya Al Kharusi; Safa Khamis Ambusaidi; Marwa Abdullah Al Raisi; Haitham Mohammed Al Mahrouqi; Asma Ali Al Kendi; Muna Mohammed Almatrushi; Mohammed Juma Al Abdali; Sanjay Jaju; Maisa Hamed Al Kiyumi (Preventive Medicine Reports)
Background: In Oman, the popularity of online food delivery services has soared since their introduction two years before the pandemic. This study aims to assess the prevalence of online food delivery service usage among Omani individuals in the Muscat region and explore its association with overweight/obesity. Methods: This is a cross-sectional study that was conducted in six randomly selected primary healthcare centres in the two most populous areas in Muscat region. Adults aged 18 years or older, who were able to read and write, and who attended the local health centre for any reason, were included. A consecutive sampling was used for enrolling subjects. A self-administered questionnaire was used and the study was conducted from January 2023 to June 2023. SPSS version 24 was used for statistical analysis. Results: A total of 467 participants were surveyed, revealing a high prevalence rate of online food delivery service usage (76.9 %,359). Younger age (P = 0.001), being single (P = 0.012), higher educational attainment (P = 0.001), absence of chronic diseases (P = 0.020),and physical inactivity (P = 0.028) were significant predictors. No association was found between online food delivery service usage and obesity/overweight (P = 0.109). While participants reported fair to good control over online food ordering, living alone emerged as a significant influencing factor, with dinner being the most commonly ordered meal. Conclusions: Our findings align with global trends, highlighting the convenience of online food services. However, the predominance of unhealthy food options raises concerns about the long-term health implications. Future research should include other regions of Oman and adopt prospective longitudinal designs.